The Influence of Store Atmosphere and Perceived Value on Consumer Repurchase Interest in Dreezel Coffee Pajajaran Branch, Bandung - Mohamad Ramdhan, Sahid; Sarah, Siti (Dinasti International Journal of Management Science, 2024)
The objective of this study was to examine the impact of store atmosphere and perceived value on consumer repurchase interest at Dreezel Coffee Pajajaran Branch, Bandung. This research utilized a quantitative methodology, incorporating a verification technique approach. Both primary and secondary data were employed in this study. A non-probability sampling method, specifically purposive sampling, was used to select participants. From a total population of 19,512 consumers who visited Dreezel Coffee Pajajaran Branch, the Slovin formula was applied to derive a sample size of 100, ensuring they met the necessary criteria. The findings indicate that store atmosphere exerts a moderate influence, evidenced by a correlation value of 0.451, while perceived value exerts a weak influence, with a correlation value of 0.246. Furthermore, the R Square value of 0.241 reveals that the two independent variables account for 24.1% of the variance in repurchase interest, with the remaining 75.9% attributed to other factors.